The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1074/jbc.m412891200
|View full text |Cite
|
Sign up to set email alerts
|

Critical Regulation of Bone Morphogenetic Protein-induced Osteoblastic Differentiation by Delta1/Jagged1-activated Notch1 Signaling

Abstract: Functional involvement of the Notch pathway in osteoblastic differentiation has been previously investigated using the truncated intracellular domain, which mimics Notch signaling by interacting with the DNAbinding protein CBF-1. However, it is unclear whether Notch ligands Delta1 and Jagged1 also induce an identical cellular response in osteoblastic differentiation. We have shown that both Delta1 and Jagged1 were expressed concomitantly with Notch1 in maturating osteoblastic cells during bone regeneration and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
144
2
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(159 citation statements)
references
References 32 publications
(45 reference statements)
11
144
2
2
Order By: Relevance
“…This gene encodes a cell surface protein called JAGGED 1, which belongs to the Delta/Serrate domain (DSL) family. Moreover, in vitro and in vivo assays have shown that JAG1 gene is expressed in osteoblastic cells during bone regeneration and its activation is also associated with increased bone mineral deposition (Nobta et al 2005). Interestingly, a recently published genome-wide association analysis identified that the rs2273061 polymorphism localized in intron 3 of the JAG1 gene was associated with the presence of variations of BMD and osteoporotic fractures in subjects of European descent and in Asian populations.…”
Section: Introductionmentioning
confidence: 99%
“…This gene encodes a cell surface protein called JAGGED 1, which belongs to the Delta/Serrate domain (DSL) family. Moreover, in vitro and in vivo assays have shown that JAG1 gene is expressed in osteoblastic cells during bone regeneration and its activation is also associated with increased bone mineral deposition (Nobta et al 2005). Interestingly, a recently published genome-wide association analysis identified that the rs2273061 polymorphism localized in intron 3 of the JAG1 gene was associated with the presence of variations of BMD and osteoporotic fractures in subjects of European descent and in Asian populations.…”
Section: Introductionmentioning
confidence: 99%
“…The reverse regulation pattern of down regulated non-adipogenic gene products (e.g. jagged 1, JAG1 correlated with osteogenesis (Nobta et al, 2005) and angiogenesis (Uyttendaele et al, 2000), CYR61 involved in angiogenesis (Lau and Lam, 1999;Schutze et al, 2005a), muscle-associated tropomyosin 1 (alpha), cysteine and glycine-rich protein 2, CSRP2, myosin heavy polypeptide 11 smooth muscle, and villin 2 A c c e p t e d M a n u s c r i p t -17 -(ezrin), VIL2 (MacLeod and Gooding, 1988;Louis et al, 1997;Babu et al, 2000;Moyen et al, 2004)) and up regulated adipogenesis-related gene products (C/EBPα, LPL and acetyl-CoA carboxylase ÎČ (Rosen et al, 2002;Wu et al, 1999;Fried et al, 1993;Spiegelman et al, 1993), and two glucose transporter molecules SLC2A3 and SLC2A14) could contribute to the switch of preosteoblasts into adipocytes during transdifferentiation. Furthermore, the initiation of transdifferentiation could involve other factors and signaling pathways that have not been described in the context of direct differentiation or whose functions have not been revealed so far.…”
Section: Accepted Manuscript -16 -mentioning
confidence: 99%
“…In an in vivo breast cancer to bone metastasis model, the presence of BMP-2 in a scaffold increased the metastatic frequency of the breast cancer cell line SUM1315 (Moreau et al, 2007). On the other hand, treatment with BMP-2 in the breast cancer cell line C2C12 resulted in increased expression of Id-1 (Katagiri et al, 1994;Nobta et al, 2005;Raida et al, 2005;Langenfeld et al, 2006), while BMP-2 also positively regulated the expression of Id-1 in certain cell contexts (Locklin et al, 2001;Takeda et al, 2004). Because BMPs have very important roles in the development of bone metastasis in prostate cancer cells (Feeley et al, 2005(Feeley et al, , 2006, it might be possible that BMP-2 in the bone environment promotes metastasis of cancer cells to bone through upregulation of the intrinsic expression of Id-1 in cancer cells.…”
mentioning
confidence: 99%